Nano‐Kirigami Structures and Branched Nanowires Fabricated by Focused Ion Beam‐Induced Milling, Bending, and Deposition (Adv. Mater. Interfaces 28/2022). Issue 28 (4th October 2022) - Xia, Deying; Notte, John
Abstract : Nano‐Kirigami Cutting of the Si3 N4 membrane is performed with a Ne or He FIB. A broad dosage from the Ga FIB then induces bending of the membrane. The He beam is optionally used grow vertical pillars before and after bending. All the images created with the He beam; center scale bar is 200 nm. This is reported by Deying Xia and John Notte in article number 2200696 .